2007
DOI: 10.1177/1359104507071090
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Patients Attending a Specialist Educational and Mental Health Service for Social Anxiety Disorders

Abstract: The purpose of this study was to evaluate the outcome of adolescents with anxiety-based school attendance problems enrolled in a specialist adolescent educational and mental health program that provides educational assistance and social skills development, and to suggest key elements that may account for its apparent effectiveness. Young people attending the Sulman Program in Sydney, Australia, between March 2003 and December 2004 were identified. Baseline information was gathered from the medical records, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 10 publications
3
4
0
1
Order By: Relevance
“…Higher ratings of prosocial functioning and a reduction in behavioural difficulties, following completion of the programme are evidence for its effectiveness. These findings replicate the overall improvements following McShane et al’s (2007) school programme. The improvement in HoNOSCA social functioning is also consistent with the results of that study, while the improvement in emotional symptoms follows McShane et al’s (2007) finding on two scales measuring a related construct.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Higher ratings of prosocial functioning and a reduction in behavioural difficulties, following completion of the programme are evidence for its effectiveness. These findings replicate the overall improvements following McShane et al’s (2007) school programme. The improvement in HoNOSCA social functioning is also consistent with the results of that study, while the improvement in emotional symptoms follows McShane et al’s (2007) finding on two scales measuring a related construct.…”
Section: Discussionsupporting
confidence: 77%
“…These findings replicate the overall improvements following McShane et al’s (2007) school programme. The improvement in HoNOSCA social functioning is also consistent with the results of that study, while the improvement in emotional symptoms follows McShane et al’s (2007) finding on two scales measuring a related construct. This study found an improvement in parental knowledge about their child’s difficulties, services and management and a pattern of improvement in behaviour at programme completion.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The school referred adolescents with anxiety-based school attendance problems to a special adolescent educational and mental health programme. Evaluation of students before and after the programme indicated that the vast majority showed improvement in social skills, stress management and overall functioning, key changes that could decrease their absenteeism and risk of dropping out (Mcshane et al, 2007).…”
Section: Servicesmentioning
confidence: 99%